PENGARUH DIKLAT, PEMBELAJARAN ORGANISASI DAN PENEMPATAN KERJA TERHADAP KINERJA PEGAWAI (Sensus pada Anggota Satuan Reserse Kriminal Polres Tasikmalaya) - Pictor Hasudungan Sitorus; H. Kartawan; Dedi Rudiana (Universitas Widyatama, 2023)
The objective of this research was to describe and analyze the influence of training, organizational learning, and placement toward performance. The method used was survey method with quantitative approach. The sample size was 71 Respondents that were an officer of Satreskrim Polres Tasikmalaya with the saturated sampling technique that gived an opportunity to all member of population as a sampel member. The data was collected by observation technique and questioner. Data Analysis technique used was path analysis. The result indicated that training, organizational learning and placement has significant effect on employee’s performances partially and simultaneously.